Painting and Illumination in Early 16th-century Ferrara: New Attributions of Miniatures to Ludovico Mazzolino - Blizniukov, Andrei L. (Actual Problems of Theory and History of Art, 2023)
The late medieval and early Renaissance book illumination of the Ferrara school has been the object of meticulous art historic studies for some generations of scholars. The relationship between the illumination and the painting is also well presented in the studies as in relation to the late 15th century. The very different situation is evident in the studies relative to the early 16th century, where the different research lines — on illumination and that on painting — are almost separated. It is evident that the most important figure related to the production of the illuminated manuscripts in the early 16th-century Ferrara was Matteo da Milano, who had yet a prestigious career before arriving in Ferrara, in his native Lombardy, and continued it with success in Rome after leaving the Este court. The three main codexes produced by the workshop of Matteo da Milano in Ferrara are Breviary of Ercole I d’Este (Modena, Biblioteca Estense and four separated full page miniatures now in Strossmayer Gallery, Zagreb), Offiziolo of Alfonso I d’Este (Lisbon, Galouste Gulbenkian Museum and fourteen separated full page miniatures now in Strossmayer Gallery, Zagreb), and the unfinished Missal of Cardinal Ippolito I d’Este (Innsbruck, University Library). These three manuscripts are enumerated between the highest masterpieces of the Italian Renaissance illumination of its latest period. The paper proposes a hypothesis that some miniatures present in the first two of the three manuscripts indicated above could be attributed to Ludovico Mazzolino. The attribution to Mazzolino allows to sustain some new theories on the initial phase of the artistic training of the master and to explain some particularities of his artistic language for the whole of his career, which find a logical explanation if we accept the hypothesis of his collaboration with Matteo da Milano. This theory also allows to focus much better than it was previously possible on the contextualization of Matteo da Milano’s work in the Ferrarese court artistic milieu.
Keywords: The late medieval and early Renaissance book illumination of the Ferrara school has been the object of meticulous art historic studies for some generations of scholars. The relationship between the illumination and the painting is also well presented in the studies as in relation to the late 15th century. The very different situation is evident in the studies relative to the early 16th century; where the different research lines — on illumination and that on painting — are almost separated. It is evident that the most important figure related to the production of the illuminated manuscripts in the early 16th-century Ferrara was Matteo da Milano; who had yet a prestigious career before arriving in Ferrara; in his native Lombardy; and continued it with success in Rome after leaving the Este court. The three main codexes produced by the workshop of Matteo da Milano in Ferrara are Breviary of Ercole I d’Este (Modena; Biblioteca Estense and four separated full page miniatures now in Strossmayer Gallery; Zagreb); Offiziolo of Alfonso I d’Este (Lisbon; Galouste Gulbenkian Museum and fourteen separated full page miniatures now in Strossmayer Gallery; and the unfinished Missal of Cardinal Ippolito I d’Este (Innsbruck; University Library). These three manuscripts are enumerated between the highest masterpieces of the Italian Renaissance illumination of its latest period. The paper proposes a hypothesis that some miniatures present in the first two of the three manuscripts indicated above could be attributed to Ludovico Mazzolino. The attribution to Mazzolino allows to sustain some new theories on the initial phase of the artistic training of the master and to explain some particularities of his artistic language for the whole of his career; which find a logical explanation if we accept the hypothesis of his collaboration with Matteo da Milano. This theory also allows to focus much better than it was previously possible on the contextualization of Matteo da Milano’s work in the Ferrarese court artistic milieu